Acute fatty liver of pregnancy: A clinical dilemma - Anita Yadav; Charu Sharma; Sukesh Kumar Kathpalia; Shiv Shankar Singh (Wolters Kluwer Medknow Publications, 2020)
Acute Fatty Liver of Pregnancy (AFLP) is a rare and life-threatening obstetric emergency. Although the exact pathogenesis is unknown, the cases of AFLP are believed to be associated with abnormal fatty acid oxidation. The diagnosis of AFLP is a challenging task for the clinicians because of the nonspecific clinical presentation which may mimic conditions such as acute viral hepatitis, preeclampsia or Hemolysis, Elevated Liver Enzymes, and Low Platelet Count (HELLP) syndrome. Early diagnosis, prompt obstetric management, intensive supportive care, and a multidisciplinary approach are the key to a good outcome. We here present two similar cases of AFLP with two different outcomes managed in a tertiary care center of the Andaman and Nicobar Islands.